“I Don’t Know the Secret Handshake”: Making Social Class Visible in a Learning Context - Michelle Anderson; Jackie Taylor; Mary Ziegler (Adult Education Research Conference, 2007)
This phenomenological study focused on the lived experience of being a mature adult pursuing a doctoral degree and having a working class background. Findings illuminate the persistent influence of social class on educational experience and the implications for adult education.